Constructing A Business Model for Islamic Digital Pension Fund: Depth Think Case Study from INTERDAP and Malaysia - Huda, Fahmi Alamil; Kurnia, Andiyani (Universitas Islam Negeri Sunan Kudus, 2022)
The objective of this paper is to redesign the Indonesian pension fund’s business model, management system, and new strategies to balance adequate profits, affordability, and sustainable programs. Consider the Malaysian pension system and adapt the INTERDAP application used by PT. Angkasa Pura II. Through this qualitative case study, we applied the foundations of the Triangle Sharia Justice Ecosystem (TSJE); Sharia, digitized the system, and supported green investment in the long run. By modeling the business strategy, facilitating the business model and supplier relationship management, and creating mutually beneficial management among stakeholders. The study found that Malaysia’s pension system has an investment purpose. Indonesia, on the other hand, provides pension loans only based on previously agreed cumulative contributions. Malaysia encourages people across the country to save on severance funds. The pension system is still managed conventionally. Malaysia requires a pension contribution of 23% of the employee’s base salary, while Indonesia requires only 3%. This will affect the contribution of pension funds to the GDP. Malaysia’s pension fund accounts for 60% of GDP. Besides, Indonesia is at only 6.03%. Another view is, to become a developed country, pension funds need to reach 60% of GDP by 2045. Because 42% of the total supply of funds in the infrastructure sector comes from pension funds. The practical implications of this study are access to information, security, and transparency in the management of pension funds through a digital system supervised by the Sharia Regulator (BPS) and the Indonesian government’s efforts to realize that supports the green economy This study integrates the foundations of the TSJE about pension funds management. The limitation of the research study is that more detailed studies and methods are needed to analyze this study. It is expected that this TSJE system will be applied further.